2020
DOI: 10.1002/jcp.29536
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of octyl gallate in alveolar macrophages cells and mice with acute lung injury

Abstract: Acute lung injury (ALI) is an inflammatory process, and has high incidence and mortality. ALI and the acute respiratory distress syndrome are two common complications worldwide that result in acute lung failure, sepsis, and death. Pro-inflammatory substances, such as cytokines and chemokines, are responsible for activating the body's defense mechanisms and usually mediate inflammatory processes. Therefore, the research of substances that decrease the uncontrolled response of organism is seen as potential for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Therefore, clearing lung inflammation and regulating immune cell components in the injured tissue are important ways to repair lung injury. 63 65 We found that the lung damage was mitigated by the treatment of MSCs, and the inflammatory cell infiltration was greatly reduced. BMSCs reprogramed monocytes and macrophages from septic lungs, producing greater amounts of IL-10, less TNF-α and IL-6, and prevented neutrophils from migrating into tissues and caused oxidative damage, thus mitigating lung damage.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, clearing lung inflammation and regulating immune cell components in the injured tissue are important ways to repair lung injury. 63 65 We found that the lung damage was mitigated by the treatment of MSCs, and the inflammatory cell infiltration was greatly reduced. BMSCs reprogramed monocytes and macrophages from septic lungs, producing greater amounts of IL-10, less TNF-α and IL-6, and prevented neutrophils from migrating into tissues and caused oxidative damage, thus mitigating lung damage.…”
Section: Discussionmentioning
confidence: 84%
“…The protective effect of quercetin on ALI involved cAMP-Epac pathway ( Wang et al, 2018 ). Furthermore, octylgallate significantly decreased the iNOS, IL-6, and IL-1β expression and protected alveolar macrophages activated with LPS and on LPS-induced ALI ( Haute et al, 2020 ). Therefore, a variety of components in QWZK could play a protective effect against ALI, and all these evidences supported the hypothesis that QWZK could play protective effects on ALI induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this compound ameliorated oxidative stress in lungs through up-regulating GSH and down-regulating ROS in LPS-induced ALI mice. Moreover, octyl gallate exerted anti-inflammatory activity through inhibiting inflammatory cytokine production (IL-1β, IL-6 and iNOS) in ALI mice and RAW264.7 stimulated by LPS [ 300 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%